Clinical characteristics of patients with cerebellar ataxia associated with anti-GAD antibodies - Tiago Silva Aguiar; Andrea Fragoso; Carolina Rouanet de Albuquerque; Patrícia de Fátima Teixeira; Marcus Vinícius Leitão de Souza; Lenita Zajdenverg; Soniza Vieira Alves-Leon; Melanie Rodacki; Marco Antônio Sales Dantas de Lima (Arquivos de Neuro-Psiquiatria)
ABSTRACT The enzyme glutamic acid decarboxylase (GAD), present in GABAergic neurons and in pancreatic beta cells, catalyzes the conversion of gamma-aminobutyric acid (GABA). The cerebellum is highly susceptible to immune-mediated mechanisms, with the potentially treatable autoimmune cerebellar ataxia associated with the GAD antibody (CA-GAD-ab) being a rare, albeit increasingly detected condition. Few cases of CA-GAD-ab have been described. Methods This retrospective and descriptive study evaluated the clinical characteristics and outcomes of patients with CA-GAD-ab. Result Three patients with cerebellar ataxia, high GAD-ab titers and autoimmune endocrine disease were identified. Patients 1 and 2 had classic stiff person syndrome and insidious-onset cerebellar ataxia, while Patient 3 had pure cerebellar ataxia with subacute onset. Patients received intravenous immunoglobulin therapy with no response in Patients 1 and 3 and partial recovery in Patient 2. Conclusion CA-GAD-ab is rare and its clinical presentation may hamper diagnosis. Clinicians should be able to recognize this potentially treatable autoimmune cerebellar ataxia.